Stille cross-coupling of secondary and tertiary α-(trifluoromethyl)-benzyl chlorides with allylstannanes. Issue 52 (11th June 2018) - Punna, Nagender; Harada, Kyosuke; Shibata, Norio
Abstract : A Stille cross-coupling reaction was developed for the first time by secondary (trifluoromethyl)benzyl chlorides and allylstannanes. Abstract : A Stille cross-coupling reaction was developed that delivers for the first time trifluoromethyl-substituted homoallyl compounds from α-(trifluoromethyl)benzyl chlorides and allylstannanes. This reaction proceeds even with low catalyst loadings (1 mol%) via a rare CF3 –Pd–π-benzyl intermediate.